Biogenic Zinc oxide nanoparticles from Celosia argentea: toward improved antioxidant, antibacterial, and anticancer activities - Alghamdi, Rana Abdullah; Al-Zahrani, Maryam Hassan; Altarjami, Lamaia R.; Al Abdulmonem, Waleed; Samir, Nadia; Said, Alaa; Shami, Ashjan A.; Mohamed, W. S.; Ezzeldien, Mohammed (Frontiers in Bioengineering and Biotechnology, 2023)
Biogenic Zinc oxide (ZnO) nanoparticles (NPs) were synthesized from Celosia argentea (C. argentea) plant extract. Structural analysis confirms the successful synthesis of biogenic zinc oxide NPs from C. argentea extract. The biogenic ZnO NPs have an average particle size of 21.55 ± 4.73 nm, a semispherical shape, and a specific surface area of about 50 m2/g. The biogenic ZnO NPs have a powerful radical scavenging activity (Ic50 = 91.24 mg/ml) comparable to ascorbic acid (ASC) as a standard (Ic50 = 14.37 mg/ml). The antibacterial efficacy was tested against gram-positive and gram-negative bacteria using an agar disc diffusion method. Gram-positive strains with biogenic ZnO NPs have a greater bactericidal impact than gram-negative strains in a concentration-dependent manner. Anticancer activity against Liver hepatocellular cells (HepG2) and Human umbilical vein endothelial cells (HUVEC) was evaluated using a [3-(4,5-dimethylthiazol-2-yl)-2,5diphenyl tetrazolium bromide] (MTT) assay. The results reflect the concentration-dependent cytotoxic effect of biogenic ZnO NPs against HepG2 cells even at low concentrations (Ic50 = 49.45 μg/ml) compared with doxorubicin (Ic50 = 14.67 μg/ml) and C. argentea extract (Ic50 = 112.24 μg/ml). The cell cycle and gene expression were analyzed to determine the potential anticancer mechanism. The flow cytometric analysis of the cell cycle revealed that biogenic ZnO NPs induce oxidative stress that activates the apoptotic genes NF-κB, CY-C, and P53, leading to cell death. The Celosia argentea improved the antioxidant, antibacterial, and anticancer activities of ZnO NPs without altering their structural properties. The effect of green synthesis on the bioactivity of biogenic ZnO NPs in vivo is recommended for future work.